Vital Analysis of Cryopreserved Sperm of Marbled Flounder, Pseudopleuronectes yokohamae - Hossen, Shaharior; Kim, Soo Cheol; Cho, Yusin; Kho, Kang Hee (Frontiers in Physiology, 2021)
The marbled flounder (Pseudopleuronectes yokohamae) is a commercial flatfish in East-Asia. The aim of the present study was to improve its sperm cryopreservation protocol based on vitality assessment of seven days and one year cryopreserved sperm. Four extenders (extender-1: sucrose solution, extender-2: glucose solution, extender-3: fish ringer’s solution, and extender-4: modified fish ringer’s solution) were tested with a combination of five cryoprotectants (dimethyl sulfoxide: Me2SO, glycerol: GLY, ethylene glycol: EG, propylene glycol: PG, and methanol: MeOH) at four different concentrations (5, 10, 12 and 15%). Fluorescent technique was applied to detect plasma membrane integrity (PMI), mitochondrial membrane potential (MMP), and DNA integrity of fresh and cryopreserved sperm. Fresh sperm was diluted at a ratio of 1:2 (sperm:extender). Post-thaw motility of sperm cryopreserved using 15% Me2SO along with either extender-1 (86.0 ± 5.2%) or extender-2 (85.7 ± 7.1%) was similar to that of fresh sperm. Sperm cryopreserved using 12% GLY combined with extender-1 (83.67 ± 6.7%) or extender-2 (83.3 ± 4.7%) showed similar motility to those cryopreserved with 15% Me2SO, but significant lower from fresh sperm. The type of straw did not show any significant difference (p > 0.05) of post-thaw sperm motility. The highest values of plasma membrane integrity (PMI) and mitochondrial membrane potential (MMP) were observed for seven days cryopreserved sperm using extender-1 in combination with 15% Me2SO (91.0 ± 2.9% and 90.0 ± 2.0%, respectively) or 12% GLY (90.0 ± 1.3% and 90.0 ± 4.6%, respectively). These results were similar to those of fresh sperm (95.3 ± 2.1% and 92.9 ± 2.5%, respectively). PMI and MMP of one year cryopreserved sperm using extender-1 in combination with 15% Me2SO (90.3 ± 2.5% and 89.3 ± 2.1%, respectively) or 12% GLY (90.0 ± 4.4% and 88.7 ± 2.2%, respectively) were significantly similar (p > 0.05) to those of fresh sperm. Sperm DNA integrity did not reveal any significant difference between fresh and cryopreserved (seven days and one year) sperm. Based on assessed sperm vitality indicators, a cryopreservation protocol using extender-1 in combination with 15% Me2SO or 12% GLY has potential for hatchery as well as to create a germplasm bank.